Power Electronics Challenges and Innovations Driven by Fast-Charging EV Infrastructure - Siddhesh Pimpale (International Journal of Intelligent Systems and Applications in Engineering, 2021)
The rapid deployment of fast-charging infrastructure is transforming the design landscape of electric vehicle (EV) power electronics. As charging speeds increase to meet consumer demand, components such as inverters, converters, and onboard chargers must adapt to higher voltages, elevated thermal loads, and stringent efficiency requirements. This paper investigates the engineering challenges posed by ultra-fast charging—particularly in thermal management, electromagnetic interference, and energy conversion efficiency—and evaluates emerging solutions including wide bandgap semiconductors (SiC, GaN), novel converter topologies, and intelligent cooling strategies. Case studies from leading EV manufacturers and charging networks illustrate real-world implementation. The study concludes with future directions in AI-optimized power electronics and grid-integrated charging systems, emphasizing the role of innovation in enhancing reliability, battery longevity, and charging performance.